Disaster Preparedness of High School Students in Red Zone and Green Zone - Emil Huriani; Adliah Wulan Sari; Tiurmaida Simandalahi (NERS Jurnal Keperawatan)
Background; Disaster mitigation was focused on the red zone that making kind of differences in students’ preparedness levels between the red zone and green zone. Meanwhile, Padang City has the potential for a Megathrust earthquake of 8.9 SR. This research aimed to determine the comparison in earthquake and tsunami disaster preparedness levels of high school students in the red and green zones